België en zijn goden kerken, religieuze groeperingen en lekenbewegingen. - Dobbelaere, Karel; Voyé, Liliane; Billiet, Jaak; Remy, Jean (Leuven Cabay, 1985)
Met Franse en Engelse samenvattingen
Keywords: 140.8 -- Wereldbeschouwing. Levensbeschouwing; 316:2 <493> -- Godsdienstsociologie--België